KAJIAN TEORITIK KRAKTERISTIK (PUMP AS TURBINE /(PAT) UNTUK PEMBANGKIT LISTRIK MICROHYDRO - Rifa'i, Ahmad Imam; Himawanto, Dwi Aries (SENATIK STT Adisutjipto, 2017)
In recent years, turbine use or pump operation as a turbine (PAT) has become an ongoing alternative to managing Water Distribution Networks (WDNs) in microhydro power generation units. Commercial pumps available on the market have a variety of shapes and models. Generally, pump manufacturers do not provide their pump characteristics curves that work as turbines. This paper presents a theoretical study on the efficiency of pump operation used as turbine (Pump as Turbine). Based on the results of the study, PAT efficiency increases with the specific speed (Nsp) and with special impeller will increase efficiency by 93% 8.07% and 5.45% and efficiency also increased by modifying the thickness of the pump blade.